what is the answer to -2/3 + 1/2?

15 Answers

Relevance
  • 4 weeks ago

    (-4+3)/6

    = -1/6

  • 4 weeks ago

    This method always works. The common denominator is the product of the two (or more denominators), 3x2 = 6 in this case. -2/3 = -4/6 and 1/2 = 3/6

    -4/6 + 3/6 = (-4+3)/6 = -1/6

  • 4 weeks ago

    -2/3 + 1/2

    (-2*2 +1*3 )/(2*3)

    =-1/6

  • 4 weeks ago

    Hi

    Denair

    (-2/3)=(-4/6)

    (1/2)=(3/6)

    (-4/6)+(3/6)= (-1/6)

    hence, the final answer is (-1/6)

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 month ago

    Ok so to find out what -2/3+1/2 is first you need to get both fractions the same denominator. In this case it is 6 because the lowest common denominator of 3 and 2 is 6.

    -2/3+1/2=?

    -2/3*(2/2)= -4/6

     1/2*(3/3)= 3/6

    -4/6+3/6= -1/6

  • 1 month ago

    When adding or subtracting fractions, you want to get the same denominator. In this case, the lowest common denominator (for 3 and 2) would be 6.

    Rewrite each fraction with a denominator of 6.

    -2/3 * (2/2) = -4/6

    1/2 * (3/3) = 3/6

    So your revised expression is:

    -4/6 + 3/6

    Now that you have the same denominator, just add the numerators:

    (-4 + 3) / 6

    = -1/6

    Answer:

    -1/6

  • 1 month ago

    - 2/3 + 1/2

    = - 2/3(2) + 1/2 (3) (to make the bottom number equal)

    = -4/6 + 3/6

    = -1/6

  • 1 month ago

    -2/3 + 1/2 = -1/6

  • 1 month ago

    -2/3 + 1/2

    -4/6 + 3/6

    (–4+3) / 6

    –1/6

  • Zirp
    Lv 7
    1 month ago

    - 1/6                                                              

Still have questions? Get your answers by asking now.